The everyday life of global finance saving and borrowing in Anglo-America - Langley, Paul, 1972- (Oxford : Oxford University Press, 2008)
In the US and the UK saving and borrowing routines have changed radically. Consumer borrowing has risen dramatically, there have been upheavals in pensions, crises of sub-prime mortgages, and an increased popularity of mutual funds. This book is an contribution to the social scientific debates about these issues and contemporary finance.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Saving and investment -- United States; Saving and investment -- Great Britain; Credit -- United States; Credit -- Great Britain